Commercially available InSb as a high-performance anode for secondary batteries towards superior lithium storage. Issue 10 (2nd August 2019) - Li, Wenying; Liu, Tingting; Zhang, Jundong; Peng, Na; Zheng, Runtian; Yu, Haoxiang; Bai, Ying; Cui, Yanhua; Shu, Jie
Abstract : This paper reports the possible application of commercially available InSb alloys as an appealing anode host for lithium storage. Abstract : Alloying lithiation hosts have aroused much more interest due to their remarkable volumetric/gravimetric capacity. Among them, Sb-based binary or ternary alloys have become an appealing anode candidate owing to their good electronic conductivity. In this work, commercially available InSb is employed as an anode host material due to its excellent electrochemical capability proved via various electrochemical tests. InSb exhibits an initial specific charge capacity of 680.9 mA h g −1 . Meanwhile, 78.6% of the initial charge capacity can be retained after the 80th cycle. By in situ X-ray diffraction (XRD), ex situ scanning electron microscopy (SEM), and ex situ transmission electron microscopy (TEM), InSb displays high structural stability and electrochemical reversibility. All these advantages suggest that InSb alloys as anode materials have great potential applications in the future.